Limnological survey of dhaka-narayanganj-demra (dnd) dam area wetlands (Bangladesh Journal of Zoology, 2020)
Present investigation was conducted to assess the physicochemical characteristics of water and its suitability for fish production at Dhaka-Narayanganj-Demra (DND) dam wetlands. Data were collected at eight points of the study area between March 2014and February 2015on temperature, transparency, pH, dissolved oxygen (DO) and free carbon dioxide (CO2) in the water. The average maximum water temperature, transparency, pH, DO, free CO2, hardness were recorded as34.6±0.4°C, 40.3±0.8cm, 7.9±0.06, 7.6±0.4 mgL-1,85.6±6.6 mgL-1 and 491.2±76mgL-1while minimum average were found as26.3±1.0°C,7.1±0.2 cm, 7.4±0.05, 5.9±0.3 mgL-1, 11.9±0.8 mgL-1 and 87.6±11.3 mgL-1respectively.All the water parameters were found in favourable condition for optimum freshwater fish production with some modification. This study can be the baseline data toward fresh fish supply and production prospect in the Dhaka city at wetland of the DND canal area.Bangladesh J. Zool. 48(1): 93-103, 2020